Emerging roles of exosomes in oral diseases progression - Jiayi Wang; Junjun Jing; Chenchen Zhou; Yi Fan (Nature Publishing Group, 2024)
Abstract Oral diseases, such as periodontitis, salivary gland diseases, and oral cancers, significantly challenge health conditions due to their detrimental effects on patient's digestive functions, pronunciation, and esthetic demands. Delayed diagnosis and non-targeted treatment profoundly influence patients' prognosis and quality of life. The exploration of innovative approaches for early detection and precise treatment represents a promising frontier in oral medicine. Exosomes, which are characterized as nanometer-sized extracellular vesicles, are secreted by virtually all types of cells. As the research continues, the complex roles of these intracellular-derived extracellular vesicles in biological processes have gradually unfolded. Exosomes have attracted attention as valuable diagnostic and therapeutic tools for their ability to transfer abundant biological cargos and their intricate involvement in multiple cellular functions. In this review, we provide an overview of the recent applications of exosomes within the field of oral diseases, focusing on inflammation-related bone diseases and oral squamous cell carcinomas. We characterize the exosome alterations and demonstrate their potential applications as biomarkers for early diagnosis, highlighting their roles as indicators in multiple oral diseases. We also summarize the promising applications of exosomes in targeted therapy and proposed future directions for the use of exosomes in clinical treatment.